The welfare cost of terrorism - Vorsina, Margarita (Terrorism and political violence, 2017)
Data from 117 countries over the period 2006 to 2011 are used to estimate a macroeconomic cross-country system of equations that examines the association between terrorism, self-reported life satisfaction, and national income. Results indicate that terrorism is negatively associated with life satisfaction, whereas no such association is found between terrorism and real GDP per worker. Stark contrasts are found, however, between OECD and non-OECD members. In all, our results suggest that the social costs of terrorism are potentially much higher than the economic costs, and measuring only the conventional economic costs of terrorism significantly underestimates the true costs.